1989
DOI: 10.3354/meps051019
|View full text |Cite
|
Sign up to set email alerts
|

Optimal foraging and density-dependent competition in marine fish larvae

Abstract: ABSTRACT. Ontogenetic migrations of fish larvae were studied in relation to vertical distribution of their prey and their predators at a single, unstratified, 60 m deep, station off Plymouth, UK. The vertical distribution of fish larvae was highly stratified. Die1 migrations were weak. Marked ontogenetic migrations reflected a size-related shlft in the equilibrium between predation and starvation risks. Yolksac larvae concentrated in the top half of the water column where planktonic predators were the least ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
3
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 40 publications
6
72
3
1
Order By: Relevance
“…Callionymidae, Scorpaenidae, Bleniidae, Labridae and Serranidae) remained in the entire water column during both the day and night. This suggests that they have not reached the development stage necessary to use the demersal habitat, given that vertical migrations of these taxa could be carried out by larger larvae (Fortier and Leggett, 1983;Fortier and Harris, 1989). This interpretation agrees in this respect with several other studies that have determined specific vertical distributions for larger larvae of certain species in offshore open waters (Leis et al, 1996;Olivar and Sabatés, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…Callionymidae, Scorpaenidae, Bleniidae, Labridae and Serranidae) remained in the entire water column during both the day and night. This suggests that they have not reached the development stage necessary to use the demersal habitat, given that vertical migrations of these taxa could be carried out by larger larvae (Fortier and Leggett, 1983;Fortier and Harris, 1989). This interpretation agrees in this respect with several other studies that have determined specific vertical distributions for larger larvae of certain species in offshore open waters (Leis et al, 1996;Olivar and Sabatés, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, to be less aggregated in the water column might be a strategy to avoid being eaten by conspecifics. Predation avoidance, by selecting depth strata of low predator abundance, has been discussed as motivation for vertical migration (Ohman et al 1983;Gliwicz 1986;Ohman 1990) and has been reported for fish larvae with respect to invertebrate predators (e.g., Yamashita et al 1985;Fortier and Harris 1989). However, nothing is known about predator avoidance with respect to conspecifics.…”
Section: Vertical Distribution Of Atlantic Mackerel Larvaementioning
confidence: 99%
“…Studies on foraging patterns and the diet of multi-specific natural assemblages of fish larvae have indicated that the degree of prey-overlap can vary (e.g. Govoni et al 1983, Jenkins 1987, Fortier & Harris 1989, Economu 1991, Gaughan & Potter 1997. Because of the high degree of morphological and behavioural variability in fish larvae, it would seem reasonable to assume that interspecific differences would have an adaptive value for the fitness of the larvae under the environmental conditions of their particular habitat.…”
Section: Introductionmentioning
confidence: 99%